A Mechanistic Review on Medicinal Mushrooms-Derived Bioactive Compounds: Potential Mycotherapy Candidates for Alleviating Neurological Disorders - Yadav, Sonu Kumar; Ir, Reshma; Jeewon, Rajesh; Doble, Mukesh; Hyde, Kevin D.; Kaliappan, Ilango; Jeyaraman, Ravindrian; Reddi, Rambabu N.; Krishnan, Jayalakshmi; Li, Min; Durairajan, Siva Sundara Kumar (Planta Medica, 2020)
According to the World Health Organization, neurological and neurodegenerative diseases are highly debilitating and pose the greatest threats to public health. Diseases of the nervous system are caused by a particular pathological process that negatively affects the central and peripheral nervous systems. These diseases also lead to the loss of neuronal cell function, which causes alterations in the nervous system structure, resulting in the degeneration or death of nerve cells throughout the body. This causes problems with movement (ataxia) and mental dysfunction (dementia), both of which are commonly observed symptoms in Alzheimerʼs disease, Parkinsonʼs disease, Huntingtonʼs disease, and multiple sclerosis. Medicinal mushrooms are higher fungi with nutraceutical properties and are low in calories and fat. They are also a rich source of nutrients and bioactive compounds such as carbohydrates, proteins, fibers, and vitamins that have been used in the treatment of many ailments. Medicinal mushrooms such as Pleurotus giganteus, Ganoderma lucidium, and Hericium erinaceus are commonly produced worldwide for use as health supplements and medicine. Medicinal mushrooms and their extracts have a large number of bioactive compounds, such as polysaccharide β-glucan, or polysaccharide-protein complexes, like lectins, lactones, terpenoids, alkaloids, antibiotics, and metal-chelating agents. This review will focus on the role of the medicinal properties of different medicinal mushrooms that contain bioactive compounds with a protective effect against neuronal dysfunction. This information will facilitate the development of drugs against neurodegenerative diseases.
Keywords: medicinal mushrooms; Cyathus; Sarcodon; Hericium; Antrodia; Ganoderma; Pleurotus; bioactive compounds; neurological disorder; neurodegenerative diseases